Refining speaking and listening skills using podcasts perfeccionando las habilidades de habla y escucha usando podcast - Prada Hernández, Victor Felipe (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This paper presents, the process followed in a case study research carried out at a private school in Tunja, with the tenth grade students. Podcasts were used as a tool to refine the listening and speaking skills, where the students evidenced some difficulties at the time of understanding speeches and conversations in class, and trying to talk about different themes. This research was based on some surveys and interviews to get the students’ responses that showed that despite of attending to a private institution where its core subject was English, they did not feel confident and expressed the lack of tools to develop these skills. Through the podcasts, learners approached to the development of these skills, because of the likingthey had for technology, and also because the activities, exercises, workshops and even tests were designed and adapted bearing inmind their likes, interests and needs.